(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2018)
In the paper, radical scavenging property of diethyl sulfoxide towards hydroxyl radical with the use of competitive reaction kinetics has been investigated. The obtained results confirm that diethyl sulfoxide compared with dimethyl sulfoxide has a greater ability to capture OH radical.